Sertania gen. nov., a new genus of butterflies (Lepidoptera: Riodinidae) from the South American dry diagonal - Kaminski, Lucas A.; Callaghan, Curtis J.; Seraphim, Noemy; Magaldi, Luiza M.; Volkmann, Luis; Freitas, André V. L. (Zootaxa, 2017)
Sertania Callaghan & Kaminski, gen. nov. is proposed for the Neotropical riodinid butterfly species “Emesis” guttata (Stichel, 1910). Both, morphological (wing shape pattern and characters in the male genitalia) and molecular data support this as a new genus distinct from all other described genera of Riodinidae. Based on morphology and molecular data, two described subspecies were raised to species status: Sertania jaibensis (Callaghan & Soares, 2001), comb. nov., stat. nov., and Sertania lambedor (P. Jauffret, J. Jauffret & Pessôa, 2008), comb. nov., stat. nov. In addition, taxonomic and ecological notes, distribution map and illustrations of adults are provided. Species in this genus are restricted to xeric environments along the South American ‘dry diagonal’ and can be a promising model for biogeography studies of Neotropical open vegetal physiognomies.